Estudio de factibilidad de un comisariato popular en la parroquia Siete de Octubre de la ciudad de Quevedo y su incidencia en las familias del sector - Álvarez Osorio, Viviana Paola (2012)
Currently the parish canton October Seven Quevedo, province of Los Rios, is a constant push and industry growth; there arises the need to establish a solid and reliable establishment where customers can buy fresh produce and a fair price. This investment project is aimed at creating a popular commissary focused on the marketing of essential items for families sector. The investment was led to the acquisition of equipment and tools necessary to achieve marketing consolidate operations required by the commissary, for normal development of the productive and commercial activities. According to the financial analysis is expected to profit from the first year to a value of $ 3,211.61, for the second year profit increases to $ 4,891.90, reaching for the fifth year the sum of $ 11,014.85; showing the strong sales performance produced at the commissary. The initial investment required for the implementation of the project is $ 28,469.70.According to market research, technical, economic and financial feasibility of the project, because it reflects the following values: an Internal Rate of Return (IRR), attractive enough 12%, when compared to lending rates in the financial market average is 5.5%. A Net Present Value (NPV), indicates that the project generates a wealth of $ 6,535.83 over the life of the project, a Cost Benefit, indicating the project is profitable because it has a B / C of 1.23, which means that for every dollar invested by the investor will get 0.23 cents of long-term recovery and long payback of 3 years and 11 months.